Quality of service and corporate image of an individual public transport company in Tacna during COVID-19 - Calderón Panigua, Dennys Geovanni (2022)
The main objective of the investigation has been to determine the degree of relationship between the quality of service and the corporate image perceived by the clients of an individual public transport company in Tacna during COVID-19, regarding the methodological aspects, it is necessary to indicate that it had a type of investigation basic, with a correlational level, quantitative approach and a non-experimental cross-sectional design, it also used the survey technique and the instrument was the questionnaire. Similarly, the population consisted of 321,351 citizens living in the province of Tacna, with a sample of 382 people and a random survey application. As a result, a Spearman's Rho value of 0.243 was obtained with a value of 0.000, which shows that there is a low positive correlation between the research variables. It was concluded by determining that the quality of service is positively and significantly related to the corporate image perceived by the clients of the individual public transport company in Tacna, denoting that prioritizing improvement actions linked to the quality of service would have an impact on increasing the corporate image that customers have, specifically those linked to empathy and security.